Michaelis-Menten Kinetics Measurements of Aldo-Keto Reductases for Various Substrates in Murine Tissue - Jakob Morgenstern; Elisabeth Kliemank; Marta Campos Campos; Peter Nawroth; Thomas Fleming (STAR Protocols, 2020)
Summary: Aldo-keto reductases (AKRs) are responsible for the detoxification of harmful aldehydes. Due to the large number of isotypes, the physiological relevance of AKRs cannot be obtained using mRNA or protein quantification, but only through the use of enzymatic assays to demonstrate functionality. Here, we present a fast and simple protocol to determine the important Michaelis-Menten kinetics of AKRs, which includes various aldehyde substrates of interest such as 4-hydroxynonenal, methylglyoxal, and malondialdehyde.For complete details on the use and execution of this protocol, please refer to Morgenstern et al. (2017) and Schumacher et al. (2018).